Are pension contributions a threat to shareholder payouts? - Armitage, Seth; Gallagher, Ronan (Journal of Corporate Finance, 2019)
UK companies have been making large contributions to reduce the deficits of their pension funds, and are believed to fund such contributions in part by reducing dividends. Using data from 2003 to 16, we find little evidence that large deficit-reduction contributions are associated with reductions in regular dividends, though we find some restraint in dividend increases and total payout. Most companies make large contributions when they have healthy cash flows and strong profitability, or inflows from disposals of assets. This suggests that the Pensions Regulator allows companies flexibility regarding the timing of contributions.